Low torque loss gears: austempered ductile iron versus carburized steel - Magalhães, Luís (2010)
Low-loss power transmission gears operate at lower temperature than conventional ones because their teeth geometry is optimized to reduce friction. The main objective of this work is to compare the operating stabilization temperature and efficiency of low-loss austempered ductile iron (ADI) and carburized steel gears. Three different low-loss tooth geometries were adopted (types 311, 411 and 611, all produced using standard 20° pressure angle tools) and corresponding steel and ADI gears were tested in a FZG machine. The results obtained showed that low-loss geometries had a significant influence on power loss, gears 611 generating lower power loss than gears 311. At low speeds (500 and 1000 rpm) and high torque ADI gears generated lower power loss than steel gears. However, at high speed and high torque (high input power and high stabilization temperature) steel gears had better efficiency.